Perspektif Hukum Keluarga Islam Mensikapi Dampak Revolusi Indusri 4.0 - Nur Rofiq; Khoiruddin Nasution; Umdatul Baroroh; Rahmawati Rahmawati; Nashih Muhammad (Iqtisad: Reconstruction of Justice and Welfare for Indonesia, 2023)
The Industrial Revolution 4.0 has a wide range of effects on people's lives and posed a challenge for families. The goal of this research is to examine the relationship between family law and the 4.0 industrial revolution, as well as the Islamic family's reaction to the impact, the function of the family, and methods to defend the family in the face with it. This type of library study was conducted using a descriptive-qualitative technique. The study's findings indicate that the relationship between family law and the Industrial Revolution 4.0 is very close, particularly in terms of moving the wheels of the economy, and that it has a favorable impact on those who know how to use it correctly. Create a detrimental influence on people who are lulled into abusing it. The effects on the family include family emphasis centered on pursuing pleasure, a lack of parental attention, excessive use of devices, the disintegration of a full family system, and materialistic existence. The family's role in mitigating the effects of the Industrial Revolution 4.0 is to apply moral values, specifically: religious function, reproductive function, socio-cultural function, protection function, love and compassion function, economic function, socialization and education function, and environmental function. Families must also be able to establish norms and cultural standards, as well as cultivate media and information literacy and create democratic family communication patterns. While the solution is to promote a mutual understanding attitude, role actualization, reward presentation, good and effective communication, instilling positive discipline, and developing a quality generation.Keywords: Islamic Family, Revolution; Industrial 4.0AbstrakRevolusi Industri 4.0 membawa berbagai dampak dalam kehidupan masyarakat dan menjadi tantangan bagi keluarga. Tujuan penelitian ini untuk menganalisis hubungan Hukum Keluarga dengan Revolusi Industri 4.0, keluarga Islam dalam mensikapi dampak, peran keluarga dan solusi mempertahankan keluarga dalam menghadapinya. Metode Penelitian yang digunakan adalah pendekatan deskriptif-kualitatif dengan jenis library research. Hasil penelitian menunjukkan hubungan hukum keluarga dengan revolusi industri 4.0 sangat erat sekali terutama dalam menggerakan roda perekonomian dan dampak positif bagi mereka yang pandai memanfaatkannya dengan bijak. Melahirkan dampak negatif bagi mereka yang terlena menyalahgunakannya. dampak dalam keluarga antara lain: konsentrasi keluarga fokus mencari kesenangan, kurang perhatian orang tua, kecenderungan memakai gawai secara berlebihan, putusnya sistem keluarga yang utuh dan kehidupan materialistis. Peran keluarga dalam memberi  perlindungan terhadap pengaruh Revolusi Industri 4.0 adalah menerapkan nilai-nilai moral (moral values) yaitu; fungsi agama, fungsi reproduksi, fungsi sosial budaya, fungsi perlindungan, fungsi cinta dan kasih sayang, fungsi ekonomi fungsi sosialisasi dan pendidikan, dan fungsi lingkungan. Keluarga juga harus mampu mengembangkan standar norma dan kultural, mengembangkan melek media dan informasi serta menanamkan pola komunikasi keluarga yang demokratis. Sedangkan solusinya ialah menumbuhkan sikap saling memahami, aktualisasi peran, menghadirkan penghargaan, komunikasi yang positif dan efektif, menanamkan sikap disiplin positif dan membangun generasi berkualitas.Kata kunci: Keluarga Islam, Revolusi; Indusri 4.0